2013
DOI: 10.4269/ajtmh.12-0760
|View full text |Cite
|
Sign up to set email alerts
|

Free-Ranging Chickens in Households in a Periurban Shantytown in Peru—Attitudes and Practices 10 Years after a Community-Based Intervention Project

Abstract: Abstract. Free-ranging chickens are often found in periurban communities in developing countries, and their feces can pose a significant public health sanitation problem. Corralling chickens raised in these periurban areas in chicken coops has been proposed previously as an intervention to address this problem. Aims of this study were to revisit households in a corralling intervention study conducted in 2000-2001 to compare poultry-raising practices and investigate current attitudes regarding the impact of rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A significant drop in poultry-raising was observed, and 81% of households no longer kept chickens in their homesteads. However, the majority of the participants (92.3%) would prefer to use corrals in poultry-raising, referencing the cleanliness of the home as the most common reason ( 253 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant drop in poultry-raising was observed, and 81% of households no longer kept chickens in their homesteads. However, the majority of the participants (92.3%) would prefer to use corrals in poultry-raising, referencing the cleanliness of the home as the most common reason ( 253 ).…”
Section: Resultsmentioning
confidence: 99%
“…participants (92.3%) would prefer to use corrals in poultryraising, referencing the cleanliness of the home as the most common reason (253).…”
Section: Natural Fermentationmentioning
confidence: 99%
“…Reducing contact with chicken faeces may be especially important, though the barriers to doing so could be substantial. Corralling chickens, for example, can incur added costs for feed and coop materials, and/or additional labour burdens—all of which may be difficult for low‐income families to bear (Harvey et al, ; Martinez et al, ). Corralling chickens may also concentrate pathogens, thus leading to greater infection (Oberhelman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 10 intervention studies identified, the only specific intervention evaluated by more than one study in the literature was corralling of poultry. 12,[28][29][30] One study revealed that children in households with corralled poultry were more likely to have Campylobacter-associated diarrhea than those who lived in households with free-roaming poultry (0.57 episodes per year vs 0.27 episodes per year, p¼0.006). 29 Another studied revealed that defecation by non-corralled chickens led to increased fecal contamination and increased feces-to-mouth episodes among children under 5 years old.…”
Section: D Zambrano Et Almentioning
confidence: 99%
“…28 Two other studies examined attitudes to and the social acceptability of poultry corralling, but not the impact of corralling on diarrheal infection. 12,30…”
Section: D Zambrano Et Almentioning
confidence: 99%